1985
DOI: 10.1172/jci112129
|View full text |Cite
|
Sign up to set email alerts
|

Substructure of human von Willebrand factor.

Abstract: Using electron microscopy, we have visualized the substructure of human von Willebrand factor (vWf) purified by two different approaches. vWf multimers, which appear as flexible strands varying in length up to 2 £m, consist of dimeric units (protomers) polymerized linearly in an end-to-end fashion through disulfide bonds. Examination of small multimers (erg., one-mers, two-mers, and three-niers) suggests that each protomer consists of two large globular end domains (22 X 6.5 nm) connected to a small central no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
139
1
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 37 publications
19
139
1
3
Order By: Relevance
“…Dimerization was initially thought to be an absolute prerequisite for the subsequent formation of intersubunit disulfide bridges linking amino-terminal domains of dimers and leading to progressive growth of the polymer chain. Structural evidence obtained with direct visualization of purified vWF multimers (48) is in agreement with these concepts, but studies with recombinant truncated mutants have suggested the possibility of alternative pathways of intersubunit assembly. In fact, a vWF molecule truncated after domain D3 (with residue Gly478 of the mature subunit representing the carboxyl terminus) still displayed intermolecular disulfide bonding, proving that the pairing of free sulfhydryl groups between aminoterminal domains of vWF may proceed independently of disulfide bond formation between carboxyl-terminal domains (49).…”
Section: Generation Of Recombinant Viruses and Transfection Of Sf9mentioning
confidence: 55%
“…Dimerization was initially thought to be an absolute prerequisite for the subsequent formation of intersubunit disulfide bridges linking amino-terminal domains of dimers and leading to progressive growth of the polymer chain. Structural evidence obtained with direct visualization of purified vWF multimers (48) is in agreement with these concepts, but studies with recombinant truncated mutants have suggested the possibility of alternative pathways of intersubunit assembly. In fact, a vWF molecule truncated after domain D3 (with residue Gly478 of the mature subunit representing the carboxyl terminus) still displayed intermolecular disulfide bonding, proving that the pairing of free sulfhydryl groups between aminoterminal domains of vWF may proceed independently of disulfide bond formation between carboxyl-terminal domains (49).…”
Section: Generation Of Recombinant Viruses and Transfection Of Sf9mentioning
confidence: 55%
“…(1), and tubules usually extend their entire length (22,23). The helical packing of the dimeric DЈD3 domains, with 4.2 repeating units per 11-nm turn, suggests that every 1 m of tubule length might correspond to a disulfide-linked multimer of Ϸ780 VWF subunits (2 subunits per repeating unit), having a mass of Ϸ195 million Da and an extended length of Ϸ47 m (Ϸ60 nm per subunit) (27). The largest plasma VWF multimers observed by gel electrophoresis or EM are perhaps one-tenth this size (27), but filaments of VWF secreted acutely by endothelial cells in culture or in vivo are often several hundred micrometers long (13,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Disassembly of the helix during granule exocytosis would then produce mature, multimeric VWF with globular domains separated by more extended polypeptide giving the appearance of beads on a string (schematic, Fig. 4F) as in rotary shadowing images (37).…”
Section: Multimeric Von Willebrand Factor Tubules Are Helical and Form Amentioning
confidence: 99%